FENOMENA POLITIK IDENTITAS DALAM PEMILU DI INDONESIA - Ridwan Wijayanto Said (DAS Institute, 2023)
The Indonesians who live on various islands have a wide range of identities. This identity is unquestionably susceptible to a variety of racism and SARA-related issues. As a consequence of this, these issues have an effect everywhere, particularly on the political front. Identity politics is a phenomenon that arises when political considerations and diversity or identity issues intersect. In Indonesia and other nations, identity politics is a frequent issue. This frequently occurs in Indonesian political elections, such as presidential, legislative, and district/city regional head elections. These issues give rise to the idea of social identity, which impacts multiculturalism. Consequently, politics in Indonesia began to intersect, resulting in various aspects being regarded as opposing. In Indonesia, a variety of examples that connect politics and identity necessitate a variety of concepts, which are then linked to issues that require investigation. After that, we discuss the various ideas and factors that cause identity politics to affect society. As a result, community and interpersonal divisions are a concern as the rise of identity politics raises issues of merit and disadvantage